Intragenic duplication in the PHKD1 gene in autosomal recessive polycystic kidney disease. Issue 1 (December 2015) - Miyazaki, Jun; Ito, Mayuko; Nishizawa, Haruki; Kato, Takema; Minami, Yukito; Inagaki, Hidehito; Ohye, Tamae; Miyata, Masafumi; Boda, Hiroko; Kiriyama, Yuka; Kuroda, Makoto; Sekiya, Takao; et al.
Abstract Background In the present study, we report on a couple who underwent prenatal genetic diagnosis for autosomal recessive polycystic kidney disease (ARPKD). Case presentation This healthy couple had previously had a healthy boy but had experienced two consecutive neonatal deaths due to respiratory distress resulting from pulmonary hypoplasia caused by oligohydramnios. The woman consulted our facility after she realized she was pregnant again. We promptly performed a carrier test for thePKHD1 gene by target exome sequencing of samples from the couple. A pathogenic mutation was identified only in the paternal allele (c.9008C>T, p.S3003F). The mutation was confirmed by Sanger sequencing of the DNA from formalin-fixed, paraffin-embedded, kidney tissue of the second neonate patient and was not found in the healthy sibling. We then performed haplotype analyses using microsatellite markers scattered throughout thePKHD1 gene. DNA from the amniocentesis was determined to belong to a carrier, and the couple decided to continue with the pregnancy, obtaining a healthy newborn. Subsequent detailed examination of the exome data suggested higher read depth at exons 45 and 46. Multiplex ligation-dependent probe amplification allowed identification of duplication of these two exons. This case suggests the potential usefulness of target exome sequencing in the prenatal diagnosis of thePKHD1 gene in ARPKD. Conclusions This is the first report of intragenic duplication in thePKHD1 gene in ARPKD.